Smoking behavior among Asian Americans during the initial phase of the COVID-19 pandemic: The influence of pandemic stressors and depression - Paula Lozano; Aven Peters; Alia Southworth; Yicklun Mo; Helen Lam; Fornessa T. Randal; Karen E. Kim (Tobacco Induced Diseases)
Introduction Heightened levels of distress among Asian Americans during the initial phases of the pandemic may be associated with current smoking behavior. In this study, we examine differences in current smoking among Asian Americans from two different ethnic backgrounds before and during the COVID-19 pandemic.